(untitled) (Journal of the College of Education for Women, 2022)
This research is concerned with qualitatively studying the history of an ancient family, one of the most prominent noble, Alawite families, that assumed the position of the Student Union for the Alawite Supervision in the city of Nishapur in Khorasan during the centries (4-6 H./ 10-12 A.H.). Thus, the research aims to investgate the historical news, and the outstanding Zubarah figures who experience the supereme the religious, historical and scientific position in Khorasan generally and Nishapur particularily. It further aims at arriving at the true meaning of the name Zubarah, and to whom it was called, and the extent of this family’s affiliation to the noble Alawi House, and how they moved to live and settle in the cities of the East, including Tabaristan and Abe, then Nishapur, and the establishment of the Alawi and student union to manage the affairs of the honorable gentlemen, take care of them to preserve lineage from confusion, and to look into religious, social and scientific affairs. Thus, the importance of the research lies in knowing everything related to the Zubarah family and what they presented during their presence in the position of the student union in the East in the service of the Prophet and the upper house. The research is like reviving a mention of the glories of this family with a pioneering role in Khorasan, especially the cities of Nishapur and Bayhaq. The research ends with a set of conclusions, such as: the name of Zubarah family goes back to its elder grandfather, Mohammad Al-Akbar, nicknamed Zubarah. This is because when he got angery on right things, his voice got higher and his face got redder, like a lion when he roars. Their affinity goes back to Al-Husseini Alawi House. Zubarah family had many followers in Nishapur and Bayhaq, who had a religious and social role and distinguished scientific contributions in various sciences and knowledge.